Nuclear acridine orange fluorescence in Rhizoctonia isolates from rice - Barrera, Viviana A. (2015)
Fil: Barrera, Viviana A. Instituto Nacional de Tecnología Agropecuaria. Instituto de Microbiología y Zoología Agrícola; Argentina.